Immune System Augmentation by Glatiramer Acetate of Peripheral Nerve Regeneration–Crush Versus Transection Models of Rat Sciatic Nerve - Luria, Shai; Cohen, Avraham; Safran, Ori; Firman, Shimon; Liebergall, Meir (Journal of Reconstructive Microsurgery, 2013)
Immune system augmentation, using the antigen glatiramer acetate (GA), which is known to affect cellular immunity, has been shown to have a positive effect on peripheral nerve regeneration. We aimed to compare the effect of GA on the regeneration of crushed versus transected nerves. Wild-type rats underwent crush or transection and repair of the sciatic nerve. They were examined 3 weeks postinjury histologically (axon count) and functionally (tibialis anterior muscle weight and footprint analysis). GA was found to augment regeneration both histologically and functionally. In the transected nerve, a significant increase in axon count distal to the injury site was seen in the GA group versus control. A similar yet statistically insignificant trend was found in the crushed nerve. Improvement was found in the footprint analysis between the GA and control groups in both crush and transected nerve groups. We found improvement in the footprint analysis in the crush versus transection group. GA was found to improve the regeneration of the peripheral nerve. Histologically, this was more pronounced in the transection injury. The discrepancy between the different functional measures examined may be explained by the distance of the reinnervated muscles evaluated from the injury site.
Keywords: nerve regeneration; peripheral nerve; sciatic nerve; neuroprotection; Glatiramer Acetate